Human pathogenic borreliae in Ixodes ricinus ticks in natural and urban ecosystem (Czech Republic) - Venclíková, Kristýna; Betášová, Lenka; Sikutová, Silvie; Jedličková, Petra; Hubálek, Zdeněk; Rudolf, Ivo (Acta parasitologica, 2014)
A total of 1279 field-collected Ixodes ricinus ticks were screened for Borrelia burgdorferi sensu lato (s.l.) in a natural and an urban ecosystem of Ostrava city (Czech Republic) by using molecular methods. Minimal prevalence rate for Borrelia burgdorferi s.l. in ticks for the urban park Bělský les was found to be 13.8% (17.6% in males, 17.8% in females and 11.7% in nymphs), similarly for the natural site Proskovice was minimal prevalence 15% (12.5% in males, 20% in females and 14.9% in nymphs). Six proven human pathogenic genomic species have been recorded in the study: B. afzelii, B. garinii, B. burgdorferi s.s., B. valaisiana, B. lusitaniae, and B. spielmanii. Emerging B. spielmanii was detected for the first time in Ixodes ricinus ticks in the region. Our results highlight the need for surveillance of zoonotic tick-borne pathogens even in urban areas.
Keywords: velkoměsta; Male; klíště; kvantitativní polymerázová řetězová reakce; Ecosystem; Česká republika; Nymph; mužské pohlaví; Real-Time Polymerase Chain Reaction; Czech Republic; nymfa; Animals; lidé; Cities; ženské pohlaví; Humans; zvířata; Ixodes; ekosystém; Borrelia; Female